2016
DOI: 10.1007/s00467-016-3314-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and cardiac dysfunction in children with chronic renal failure on regular hemodialysis

Abstract: Significant oxidative stress was present in children with ESRD and was correlated with the degree of cardiac dysfunction detected early using the new cardiac imaging modality, STE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…There are only a limited number of clinical studies investigating the direct link between oxidative/nitrative stress and the development of LVH and heart failure in T4CRS. In a clinical cohort study, plasma GSH levels correlated with the degree of cardiac dysfunction checked by speckle tracking echocardiography in children with ESRD (Al-Biltagi et al, 2016 ). In another study, a cross-sectional analysis recruiting 78 adults with stage 3-4 CKD (eGFR: 25–60 mL/min) revealed that elevated plasma F2-isoprostane level as a marker of oxidative stress was associated with reduced heart rate variability (Fadaee et al, 2017 ).…”
Section: Pathways Of Cardiac Oxidative/nitrative Stress In T4crsmentioning
confidence: 99%
“…There are only a limited number of clinical studies investigating the direct link between oxidative/nitrative stress and the development of LVH and heart failure in T4CRS. In a clinical cohort study, plasma GSH levels correlated with the degree of cardiac dysfunction checked by speckle tracking echocardiography in children with ESRD (Al-Biltagi et al, 2016 ). In another study, a cross-sectional analysis recruiting 78 adults with stage 3-4 CKD (eGFR: 25–60 mL/min) revealed that elevated plasma F2-isoprostane level as a marker of oxidative stress was associated with reduced heart rate variability (Fadaee et al, 2017 ).…”
Section: Pathways Of Cardiac Oxidative/nitrative Stress In T4crsmentioning
confidence: 99%
“…The risk of cardiovascular diseases (CVD) increases even in the early stages of CKD [ 4 ]. The pathogenesis of CVD in patients with CKD is complex and consists of traditional (e.g., arterial hypertension (AH) and diabetes mellitus (DM)) and uraemia-specific (e.g., oxidative stress, protein carbamylation, increased fibroblast growth factor 23 levels, anaemia and altered calcium and phosphate metabolism) factors [ 4 , 5 ]. CKD causes type 4 cardiorenal syndrome which is characterised by left ventricular (LV) hypertrophy, diastolic dysfunction (DD), deteriorated systolic heart function and increased risk of cardiovascular events [ 6 , 7 ].…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is considered as the predominant cause of mortality and morbidity in chronic kidney disease (CKD) patients [1]. Left ventricular diastolic and systolic dysfunction and left ventricular hypertrophy (LVH) contribute to the increased cardiovascular mortality rate in these patients [2, 3]. Such changes have been observed in young adults and children on prolonged dialysis [46].…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial function and LVH in CKD patients have been studied using conventional pulsed-wave Doppler echocardiography (cPWD) in both pediatric and adult patients on regular HD, and this method evaluates hydrodynamic responses, which are load-dependent, making it disadvantageous in end-stage renal disease (ESRD), where fluid status may change according to the patient’s condition [26]. Conventional pulsed-wave Doppler echocardiography only allows partially subjective semi-quantitative measurements.…”
Section: Introductionmentioning
confidence: 99%